Zed attack proxy cookbook : hacking tactics, techniques, and procedures for testing web applications and APIs using OWASP ZAP /: hacking tactics, techniques, and procedures for testing web applications and APIs using OWASP ZAP. (2023) - Soper, Ryan; Torres, Nèstor; Almoailu, Ahmed
No abstract available